Peran Guru Sebagai Motivator Dalam Meningkatkan Minat Belajar Siswa Di SD Negeri 012 Minas Barat - Guci, Ade Aswanidar; Kirana, Candra (Journal of Sustainable Education, 2025)
This study aims to explore the role of teachers as motivators in enhancing students' learning interest at SD Negeri 012 Minas Barat. Using a descriptive qualitative approach, the research provides an in-depth examination of student motivation within the educational context. Data were collected through in-depth interviews with the principal, teachers, and students, as well as observations and related documentation. The findings reveal that the role of teachers as motivators is crucial in creating an engaging and supportive learning environment. Factors such as positive encouragement, fostering learning interest, modeling behavior, providing a conducive learning environment, and constructive feedback are found to significantly influence student motivation. The study also identifies several challenges faced by teachers, such as a lack of teaching skills and understanding of student motivation. Efforts to enhance teacher competencies, develop students' skills, and strengthen communication and support among teachers, students, and parents are proposed as solutions to address these challenges. This research offers valuable insights for educators and education stakeholders on effective strategies to boost students' learning interest through the motivational role of teachers.